Assistive Technology Deficit and Pedagogical Stagnation: A Tam-Samr Analysis of EdTech Integration for Inclusive Education in Private Primary Schools in Abuja - Adedapo, Adeyemi; Arogundade, Ekundayo Deborah (NIU Journal of Humanities, 2026)
The enormous potential of Educational Technology (EdTech) for promoting inclusive education often remains unrealized in resource-restricted environments, where the systemic factors limit both the adoption and innovative utilisation of technology in educational settings. This study identifies system-level barriers to the adoption of EdTech tools for inclusive education in private primary schools in Abuja, Nigeria. In contrast to the availability-focused evaluations, the research adopts the Technology Acceptance Model (TAM) and SAMR (Substitution, Augmentation, Modification, Redefinition) model to assess not only the availability but also the incorporation of EdTech into pedagogical processes. For data collection, a cross-sectional survey was conducted among 697 participants (497 pupils, 176 teachers, and 24 school administrators) in 24 private primary schools selected in three wards of the Abuja Municipal Area Council on purpose, with respect to three key inclusion criteria (at least five years of existence, the presence of some kind of technology infrastructure, such as computers or projectors, and proprietor permission to participate in the research). Data collection was done using three questionnaires (for pupils, teachers, and administrators), with questions organised into six sections, which include evaluation of the availability of technologies, teachers' skills, pedagogical use of technologies (SAMR-related questions), and TAM constructs (Perceived Usefulness and Perceived Ease of Use). The content validity of the questionnaires was ensured through expert review, while reliability was estimated with the help of Cronbach’s alpha (with values ranging from 0.76 to 0.84 for subscales). Findings have shown a twofold gap: a relatively high level of adoption of general-purpose EdTech tools, as evidenced by the use of interactive whiteboards in roughly 66% of schools, and a critical shortage of assistive technologies, as evidenced by the total lack of speech-to-text tool usage by students. Pedagogically, the use of EdTech tools was primarily at the level of Substitution and Augmentation of SAMR model, with 68.6% of teachers used EdTech for individualized instruction.  This study identifies two significant obstacles to inclusive education: a continuing gap between the availability of assistive technologies and the superficial incorporation of EdTech into pedagogical practice. The report proposes a mandatory inclusive EdTech framework that incorporates competency-based transformative teacher training, ring-fenced financing for assistive technologies, and required technical support to address this issue. Keywords: Educational Technology, Inclusive Education, Assistive Technology, Technology Integration, TAM, SAMR.